To divide a fraction by a fraction you multiply the first fraction, or dividend (number being divided), by the reciprocal (reversed, numerator becomes denominator and denominator becomes numerator) of the divisor (number dividing the divisor). In this case, 6/7 would be multiplied by 7/36 and the answer would be 42/252, which can be reduced to 1/6. Hope this helps :)
Chat with our AI personalities
That depends on the order in which the problem is expressed:(36 / 6) / 7 = 6 / 736 / (6 / 7) = 42
6/7 = 36/42.
-5/12 divided by 15/7 = -7/36
6*(6/7) = 6*6/7 = 36/7 or 51/7.
6/7 * 6/13 = (6*6)/(7*13) = 36/91